PENGARUH PEMBELAJARAN KOOPERATIF TEKNIK TARI BAMBU TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK ORGANISASI KEHIDUPAN - Detrysia Aryanti; Pramudiyanti Pramudiyanti; Berti Yolida (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
Studying-result is the final aim on learning process which is closely related to the on field-studying. Observations in VII Grade of Public Junior High 2 Jati Agung shows low on result and activity of learning. This research was aimed to know the influences of Bamboo Dancing. The design was equivalen control group. This research's data was quantitative and qualitative. The sample was Class VIIA and VIIB which selected by cluster random sampling. Quantitative data obtained average value of the pretest, posttest and N-gain on Life Organization matter.  Qualitative data obtained percentage average of students activities and responses of using Bamboo Dancing was analyzed descriptively. The results of the research show that Bamboo Dancing increasing the activity of the student with good criteria which is on 76.62% , it is also evident from the increase observed for all aspects. The Study-result from the experiment class is increasing too, with N-gain average (0.154) shows the high criteria. Besides, all of the student gave positive response to the Bamboo Dancing . Thus, it can be concluded that the uses Bamboo Dancing is influential in increasing the Study and activity result.Key words: bamboo dancing, life organization, student study results and learning activity.